El sistema de control interno en el Área de Contabilidad y su incidencia en la gestión administrativa y operativa de las empresas constructoras de la ciudad de Trujillo, año 2015. - Aredo Rodriguez, Edwin Josmell (2016)
This research focuses on the design of an internal control system in the accounting area construction companies in the city of Trujillo and how influence is in the administrative and operational management, therefore the company was chosen as sample Constructora e Inversiones Soto SAC. To carry out this research, we proceeded to use various tools such as surveys, interviews to analyze, evaluate and get a diagnosis of the situation of internal controls in the accounting area Constructora e Inversiones Soto SAC thus many shortcomings in the organization and implementation of activities of the accounting area, therefore made it very difficult presenting the information in a timely manner, accurate and reliable to management for decision making was found. Given the situation described above, it is proposed to design an internal control system in the area of accounting, which will be based on the COSO model, which contains five components such as; control environment, risk assessment, control activities, information and communication and monitoring activities. Also worth noting is being proposed policies, procedures and processes that help to improve internal controls and accounting area so we can have updated and sorted all the information and thus provide information that will help the various operational areas and management management to safeguard each of the resources available to the company.